2004
DOI: 10.1021/om049360b
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Deactivation of Neutral Nickel Ethylene Polymerization Catalysts in the Presence of Functionalized Olefins

Abstract: Materials and Methods. All reactions were set up in a nitrogen glovebox. Methyl acrylate, and allylbenzene were purchased from the Sigma-Aldrich Chemical Company, Milwaukee, WI. They were dried over CaH 2 and distilled under reduced pressure. Methyl acrylate 2,3,3-d 3 and toluene-d 8 were purchased from Cambridge Isotope Laboratories, Inc., Andover, MA. Methyl acrylate 2,3,3-d 3 was used as received. Toluene-d 8 was dried over Na 0 /benzophenone and distilled under reduced pressure. The synthesis of compound 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 16 publications
5
42
0
Order By: Relevance
“…In contrast, the solution of 3c-Na remained the same bright orange before and after polymerization. Grubbs and co-workers have reported previously that the formation of nickel bis­(phenoxyimine) ligand complexes is a common catalyst deactivation pathway . Alternatively, Mecking and co-workers have proposed that bimolecular elimination of nickel alkyl and/or nickel hydride species can also be major decomposition routes .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In contrast, the solution of 3c-Na remained the same bright orange before and after polymerization. Grubbs and co-workers have reported previously that the formation of nickel bis­(phenoxyimine) ligand complexes is a common catalyst deactivation pathway . Alternatively, Mecking and co-workers have proposed that bimolecular elimination of nickel alkyl and/or nickel hydride species can also be major decomposition routes .…”
Section: Resultssupporting
confidence: 75%
“…When polar olefins such as VA and AA were added to a solution containing 3d /B­(C 6 F 5 ) 3 , the initial bright orange solution became noticeably lighter in color. Surprisingly, upon further exposure to ethylene for up to 16 h, no polymer products were obtaind. , The change in solution color and the absence of polymerization activity suggest that 3d is not stable in the presence of polar vinyl olefins.…”
Section: Resultsmentioning
confidence: 99%
“…In these systems, neutral nickel complexes with five-membered-ring chelating structure such as anilinotoropone [29][30][31] and anilinoperinaphthenone [32] ligands showed higher activity for ethylene polymerization than those with six-membered ones. Although it is not obvious how the chelate size affects the catalytic activities, the decrease in polymerization activity was observed with the expansion of chelate size in the other systems reported by Keim and Schulz [33], Grubbs and coworkers [10][11][12][13][14], and Brookhart [29][30][31][32].…”
Section: Introductionmentioning
confidence: 87%
“…Neutral nickel catalysts have attracted much attention, because they show good activities for olefin polymerization without any cocatalysts [10][11][12][13][14]. These catalysts are tolerant for polar solvents such as water, therefore they are useful for copolymerization of olefin with polar monomers [15][16][17] and emulsion polymerizations [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Early examples of SHOP type neutral nickel catalysts have been commercialized for the synthesis of α-olefins [22,23,24]. A series of neutral nickel catalysts bearing salicylaldimine ligands (Chart 1 A ) was reported by Grubbs et al, which showed excellent tolerance towards polar monomers to give functionalized polyethylene [25,26,27,28]. The β-ketoiminato neutral nickel complexes with six-membered-ring were synthesized and applied as the olefin ( co )polymerization catalyst (Chart 1 B ) [29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%